The Expression of the Chemokine CXCL14 Correlates with Several Aggressive Aspects of Glioblastoma and Promotes Key Properties of Glioblastoma Cells - Fazi, Barbara (Int J Mol Sci, 2019)
Glioblastoma (GBM) is a primary brain tumor whose prognosis is inevitably dismal, leading patients to death in about 15 months from diagnosis. Tumor cells in the mass of the neoplasm are in continuous exchange with cells of the stromal microenvironment, through the production of soluble molecules, among which chemokines play prominent roles. CXCL14 is a chemokine with a pro-tumor role in breast and prostate carcinoma, where it is secreted by cancer associated fibroblasts, and contributes to tumor growth and invasion. We previously observed that CXCL14 expression is higher in GBM tissues than in healthy white matter. Here, we study the effects of exogenously supplemented CXCL14 on key tumorigenic properties of human GBM cell lines. We show that CXCL14 enhances the migration ability and the proliferation of U87MG and LN229 GBM cell lines. None of these effects was affected by the use of AMD3100, an inhibitor of CXCR4 receptor, suggesting that the observed CXCL14 effects are not mediated by this receptor. We also provide evidence that CXCL14 enhances the sphere-forming ability of glioblastoma stem cells, considered the initiating cells, and is responsible for tumor onset, growth and recurrence. In support of our in vitro results, we present data from several GBM expression datasets, demonstrating that CXCL14 expression is inversely correlated with overall survival, that it is enriched at the leading edge of the tumors and in infiltrating tumor areas, and it characterizes mesenchymal and NON G-CIMP tumors, known to have a particularly bad prognosis. Overall, our results point to CXCL14 as a protumorigenic chemokine in GBM.